"Living high - training low" vs. "living high - training high": erythropoietic responses and performance of adolescent cross-country skiers - Christoulas, K.; Karamouzis, M.; Mandroukas, K. (The Journal of Sports Medicine and Physical Fitness, 2011)
AIM: To determine and compare the erythropoietic response and exercise performance of adolescent cross-country skiers, as a result of "living high-training high" (HH) and "living high-training low" (HL). METHODS: Nine female and six male adolescent cross-country skiers volunteered to participate in separate trials. In the first trial (HH), the skiers lived and trained for 21 days at 1550-2050 m, while in the second trial (HL) they trained near sea level (450-500 m) but resided at 1550 m. All participants underwent maximal cycle ergometer tests for the determination of VO2max and cardiorespiratory parameters via an open circuit system at sea level before ascent to altitude, and 1-2 days after descent from altitude. Blood samples were drawn prior to and immediately after maximal cycle exercise testing, at sea level prior to ascent, on days 1 (D1) and 21 (D21) at altitude (1740 m), and 1-2 days post-altitude, for the determination of serum erythropoietin (EPO) concentration, haemoglobin (Hb), hematocrit (Ht), and red blood cell (RBC) volume. RESULTS: The results showed that both boys and girls cross-country skiers, significantly improved their sea level VO2max after 21 days of living at moderate altitude and training near sea level. CONCLUSION: The present study demonstrates that living at moderate altitude, 1550-2050 m and training low, near sea level (450-500 m) significantly increases VO2max and RBC mass for both boys and girls. Results indicate that applying the training concept "living high - training low" in adolescent athletes may improve their endurance performance.